Using Toulmin's Argument Pattern on Problem Solving Model to Improve Problem-Solving Analysis Ability: Learning Alternatives During the Covid-19 Pandemic - Dwikoranto Dwikoranto (IJORER : International Journal of Recent Educational Research, 2022)
The lecture process even in the Covid-19 pandemic must continue. The right of students to obtain good teaching must still be fulfilled. Lectures are conducted online using the Zoom, WhatsApp, Google Drive, Google Form platforms. The platform is assembled in a problem solving model with Toulmin's Argument Pattern. Problem solving analytical skills are the main focus of the Statistics course. This study aims to improve students' analytical problem solving skills, describe their improvement and describe student responses with Toulmin's Argument Pattern in problem solving models. The research design used a one group pre-test and post-test design. The research subjects were 30 students of the Unesa Physics Department. The instruments used in collecting data include: (1) problem solving analysis ability test sheets, (2) student response questionnaires. The research data scores that have been collected after going through a series of prerequisite tests, normality tests and homogeneity tests are then analyzed using paired t-tests to find out if there are differences in pre-test scores and post-test scores for solving analytical skills. student problems. The mean level of improvement in pre-test scores and post-test scores was calculated using normalized gain. The results showed an increase in problem-solving analytical skills in the medium and high categories. Student responses in lectures were very positive.